Web campaigning - Foot, Kirsten A. (Acting with technology., 2006)
"The use of the Web in U.S. political campaigns has developed dramatically over the course of the last several election seasons. In Web Campaigning, Kirsten Foot and Steven Schneider examine the evolution of campaigns' Web practices, based on hundreds of campaign Web sites produced by a range of political actors during the U.S. elections of 2000, 2002, and 2004. Their developmental analyses of how and why campaign organizations create specific online structures illuminates the reciprocal relationship between these production practices and the structures of both the campaign organization and the electoral arena. This practice-based approach and the focus on campaigns as Web producers make the book a significant methodological and theoretical contribution to both science and technology studies and political communication scholarship. Foot and Schneider explore the inherent tension between the desire of campaigns to maintain control over messages and resources and the generally decentralizing dynamic of Web-based communication. They analyze specific strategies by which campaigns mitigate this, examining the ways that the production techniques, coproducing Web content, online-offline convergence, and linking to other Web sites mediate the practices of informing, involving, connecting, and mobilizing supporters. Their conclusions about the past decade's trajectory of Web campaigning point the way to a political theory of technology and a technologically grounded theory of electoral politics. A digital installation available on the web illustrates core concepts discussed in the text of the book with examples drawn from archived campaign Web sites. Users have the opportunity to search these concepts in the context of fully operational campaign sites, recreating the Web experience of users during the election periods covered in the book."